Exploration of the integration of Lean and environmental improvement - Biggs, Claire (Cranfield University, 2009)
With increasing awareness of the environmental damage that is occurring as a result of human activities, there are also increasing pressures on manufacturing companies to reduce environmental impacts. Many environmental impact reduction methods contain some element of waste reduction, which is also the focus of Lean manufacturing, although their definitions of waste differ somewhat. The aim of this research was to investigate the synergies and similarities between Lean manufacturing and environmental impact reduction in manufacturing, with a strong focus on practical implications. The research was carried out in three stages: a review of the relevant literature, an exploration stage which consisted of semi-structured interviews with ten companies, and action research studies with two companies, investigating company reactions to the introduction of environmental impact reduction measures into their Lean implementation, via adapted tools designed using data from the literature review and exploration stage. Findings from all the research stages were analysed and synthesised, producing a total of 54 findings (including answers to research questions, notes for practitioners, and suggestions for future work) across 12 themes. The research confirmed that some environmental improvement occurs as a side effect of Lean implementations; compared Lean and environmental wastes; looked at potential benefits of mapping for environmental improvement within Lean implementations; found that Lean can be used as a framework for other changes, including environmental improvement; identified opportunities for adoption or adaptation of particular Lean tools for environmental impact reduction; identified new ways in which Lean acts as a foundation for change; showed common uses for goals and measures; found that workforce involvement was an important factor, as was education and training; identified some factors for acceptance and adoption; discussed the effectiveness of integrated implementation; and discussed the benefits of holistic integration of Lean and environmental improvement.